Carbides of A³B⁵ compounds – new class materials for opto- and microelectronics - Osinsky, V.I.; Masol, I.V.; Lyahova, N.N.; Deminsky, P.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Discussed in this paper are options for replacing the virtual structure of SiC
atoms with AlN compound. The Al₄C₃, AlNC and AlNOC compounds in vapor and solid
epitaxial processes have been obtained as a result of carbothermic reduction. Analized is
the role of precursors in the way of reducing the formation temperature for stable phases
of aluminum oxynitrocarbide during epitaxy of aluminum nitride in the presence of
carbon atoms. The dependence on preparation conditions for the aluminum single
oxycarbide crystal structure has been explored. The influence of partial 2H-SiC crystal
structure on the state of the single oxycarbide crystal structure was determined. The
semiconductor AlNOC has been experimentally obtained.